Variations in pink-shrimps Farfantepenaeus brasiliensis and F. paulensis juvenile abundance: clarifying ecological patterns and providing subsidies to management in shallow marine ecosystems - Perroca, Júlia Fernandes [UNESP]; Rodrigues Filho, Jorge Luiz; Fransozo, Adilson [UNESP]; Costa, Rogerio Caetano da [UNESP] (Elsevier, 2022)
In Brazilian marine ecosystems, Farfantepenaeus brasiliensis and F. paulensis are caught around 40-meter isobath, whereas in shallower waters (<20 m), juveniles are caught as bycatch in fisheries targeting other shrimp species. Despite their importance in fisheries, the ecology of the two Farfantepenaeus species is not well understood. Their recruitment patterns still are not clear and both species in adult phase are landed as pink shrimp, making evaluations impossible. In this study, we focused on evaluating a 23-year fisheries-independent dataset, seeking to clarify recruitment patterns and to relate them to El Niño Southern Oscillation events and environmental factors in the Ubatuba Bay, a traditional trawling area in Southeast Brazil. Generalized Additive Models indicated that both species shared some patterns in early life stages, being more abundant between January to April, when granulometry presented Phi ≤ 4.5, and salinities and temperatures are higher than 35 and 25 ºC, respectively. Also F. paulensis abundance increased under El Niño events. The higher capture of Farfantepenaeus spp. in a period with intense trawling activity and prior to the closed season (March to May) indicated that populations are not adequately protected in the study area. Beyond highlighting the role of shallow marine areas as potential nursery ecosystems for species of pink shrimp, these results provide evidence to support the fishing closed season in the southeastern and southern regions of Brazil.
Keywords: Artisanal fisheries regulation; ENSO; GAM; Penaeoidea; Species conservation